2019
DOI: 10.1542/peds.2019-2203
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Capability of Hospitals to Provide Definitive Acute Care for Children: 2008 to 2016

Abstract: BACKGROUND: Provision of high-quality care to acutely ill and injured children is a challenge to US hospitals because many have low pediatric volume. Delineating national trends in definitive pediatric acute care would inform improvements in care. METHODS: We analyzed emergency department (ED) visits by children between 2008 and 2016 in the Nationwide Emergency Department Sample, a weighted sample of 20% of EDs nationally. For each hospital annually, we determined the Hospital Capability Index (HCI) to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
70
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 47 publications
(60 reference statements)
2
70
1
Order By: Relevance
“…[1][2][3] Contributing to this challenge are the facts that actual pediatric critical care is uncommon (when compared to the adult population), the distribution of where children seek emergency medical care and who is there to care for them varies, and there are many competing demands on a health care providers' initial and continuing medical education. [4][5][6][7][8][9][10][11] Further compounding these facts is the variation in the rate and quality of procedural skill acquisition amongst each individual learner. This supports the need to utilize varied educational modalities and providing customizable frequencies of practice to meets all learners' needs.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Contributing to this challenge are the facts that actual pediatric critical care is uncommon (when compared to the adult population), the distribution of where children seek emergency medical care and who is there to care for them varies, and there are many competing demands on a health care providers' initial and continuing medical education. [4][5][6][7][8][9][10][11] Further compounding these facts is the variation in the rate and quality of procedural skill acquisition amongst each individual learner. This supports the need to utilize varied educational modalities and providing customizable frequencies of practice to meets all learners' needs.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Pediatrics, Michelson et al 1 quantified what many of us who practice pediatric emergency medicine have suspected: that many hospitals have reduced their pediatric inpatient capability, which has necessitated the need for children to be transferred for definitive care, often outside of their home communities. They further identified that hospitals with emergency departments (EDs) that care for few pediatric patients are least likely to offer inpatient services and that pediatric inpatient care is becoming concentrated in highervolume urban centers, particularly primary pediatric facilities.…”
mentioning
confidence: 99%
“…They further identified that hospitals with emergency departments (EDs) that care for few pediatric patients are least likely to offer inpatient services and that pediatric inpatient care is becoming concentrated in highervolume urban centers, particularly primary pediatric facilities. 1 In this study, the Healthcare Cost and Utilization Project Nationwide Emergency Department Sample database from 2008 to 2016 was used to sample EDs nationally for admission rates and transfers. This sample represented 21.8 million pediatric ED visits in 2008 and 24.1 million visits in 2016.…”
mentioning
confidence: 99%
See 2 more Smart Citations